Psoriasis and its impact on the clinical outcome of patients with pulmonary embolism - Keller, Karsten; Hobohm, Lukas; Ostad, Mir A.; Karbach, Susanne; Espinola-Klein, Christine; Münzel, Thomas; Gelfand, Joel M.; Konstantinides, Stavros V.; Steinbrink, Kerstin; Gori, Tommaso (International journal of cardiology, 2021)
Background - An increased risk for venous thromboembolism (VTE), comprising pulmonary embolism (PE) and deep venous thrombosis, has been reported in psoriasis patients. The impact of psoriasis on prognosis of VTE patients is widely unknown. - Methods - Hospitalized PE patients were stratified for psoriasis and the impact of psoriasis on outcome was investigated in the German nationwide inpatient sample of the years 2005-2017. - Results - Overall, 1,076,384 hospitalizations of PE patients (53.7% females, median age 72.0 [60.0-80.0] years) were recorded in Germany 2005-2017. Among these, 3145 patients had psoriasis (0.3%). Psoriatic PE patients were younger (68.0 [57.0-76.0] vs. 72.0 [60.0-80.0] years,P < 0.001) and more often male (64.1% vs. 46.3%,P < 0.001). The prevalence of VTE risk factors, traditional cardiovascular risk factors and cardiovascular comorbidities was higher in psoriatic than in non-psoriatic individuals. Psoriatic PE patients showed a lower in-hospital case-fatality rate (11.1% vs. 16.0%,P < 0.001), confirmed by logistic regressions showing an independent association of psoriasis with reduced case-fatality rate (OR 0.73 [95%CI 0.65-0.82],P < 0.001), despite higher prevalence of pneumonia (24.8% vs. 23.2%,P = 0.029). Psoriasis was an independent predictor for gastro-intestinal bleeding (OR 1.35 [95%CI 1.04-1.75],P = 0.023) and transfusion of blood constituents (OR 1.23 [95%CI 1.11-1.36],P < 0.001). - Conclusions - PE patients with psoriasis were hospitalized in median four years earlier than those without. Although psoriasis was associated with an unfavorable cardiovascular-risk and VTE-risk profile in PE patients, our data demonstrate a lower in-hospital mortality in psoriatic PE, which might be mainly driven by younger age. Our findings may improve the clinical management of these patients and contribute evidence for relevant systemic manifestation of psoriasis. - Translational perspective - An increased risk for venous thromboembolism (VTE), comprising pulmonary embolism (PE) and deep venous thrombosis, has been reported in psoriasis patients, but the impact of psoriasis on prognosis of VTE patients is widely unknown. PE patients with psoriasis were younger and psoriasis was associated with an unfavorable cardiovascular-risk and VTE-risk profile. In-hospital mortality was lower in psoriatic PE patients, which might be mainly driven by younger age. Our findings improve the clinical management of PE patients and contribute evidence for relevant systemic manifestation of psoriasis. - One sentence summary - Psoriasis with chronic inflammation promotes PE development, is associated with an unfavorable cardiovascular and VTE-risk profile, but lower in-hospital mortality.